Islamic Corporate Social Responsibility: CSR Practices by Islamic Microfinance Institutions in Lampung - Irawan, Endri; Ambarwati, Diana (Journal of Contemporary Applied Islamic Philanthropy, 2023)
Purpose: This article describes the practice of corporate social responsibility (CSR) adopted by Baitul Maal Wa Tamwil (BMT) in Lampung. This study also examines the literature on different views of CSR and how CSR can be rooted in organizational strategy so that it becomes an organizational competitive advantage. Methodology: A descriptive qualitative method was used in this study, in which the researchers conducted in-depth interviews with both BMT employees and beneficiary communities. Findings: This study found that Baitul Maal Wa Tamwil, which became the locus of research, namely BMT Assyafiiyah Berkah Nasional carries out CSR corporate social responsibility in several forms of programs both physical, facilitating and empowering in nature. The physical form is carried out by providing assistance for the construction of places of worship, Islamic boarding schools, the construction of drilled wells and a program to renovate livable houses. The form of facilitation is carried out by providing compensation, giving OTP (Sponsoring Parents), giving TPA incentives, community service cars and productive forms by giving rolling goats and providing business capital with a qordul hasan contract. This study recommends the need to increase the involvement of baitul maal wattamwil in the process of economic development in general, because the practice of corporate social responsibility will contribute not only to increasing the company's competitive advantage but also to increasing community empowerment. For the company, CSR will also ensure the company's sustainable growth due to improved image and increased customers leading to increased profitability.